Development of Al-Gr-Ca hybrid composite for braking application. (2021) - Vignesh Kumar, P.; Nithiyapathi, C.; Daniel Das, A.; Preethi, V.
Abstract: This research deals with development of hybrid aluminium composite through traditional stir casting route. Varying weight percentage of alumina (8% & 12%) and constant weight of graphite (5%) are choosen to improve the basic and friction behaviour of aluminum .Pin on disc tribometer was utlized to under the wear behvaiour of developed composite at constant wear parameter viz constant load, velocity, and slding distance. The output showed that addition of reinforcement increase the hardness of fabricated composite. Likewise incremental percentage of alumina improvise the wear resistance of composite, this might be owing the addition of solid lubricants that forms tribo layer between the pin and contour disc parts.